Impacts of natural disasters on households and small businesses in India. - Patankar, Archana; Joshi, Kaushal (Economics working papers, 2019)
Extreme precipitation and flooding cause large scale impacts on people, and are further intensified by rapid urbanization, infrastructure expansion, and large numbers of people residing in informal settlements in destitute conditions. This underscores the need to characterize the impacts of extreme precipitation on different stakeholders and help formulate policies and plans to mitigate them. The focus of this paper is on characterizing and analyzing the impacts of extreme precipitation events at the micro level on vulnerable households and small and medium-sized enterprises in three locations in India: Mumbai, Chennai, and Puri district. These areas have faced devastating extreme rainfall events in recent years and offer critical insights into asset the exposure of, and direct and indirect impacts on, urban and rural entities. The flood impact analysis in this paper provides a multidimensional view with quantitative damage estimates and qualitative insights into the devastation and distress caused. It also highlights the heterogeneity of flood impacts and the potential to push the poor into a debt trap and further poverty